2017
DOI: 10.1016/j.bbagen.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the molecular function of human [2Fe-2S] BOLA1-GRX5 and [2Fe-2S] BOLA3-GRX5 complexes

Abstract: Members of the monothiol glutaredoxin family and members of the BolA-like protein family have recently emerged as specific interacting partners involved in iron-sulfur protein maturation and redox regulation pathways. It is known that human mitochondrial BOLA1 and BOLA3 form [2Fe-2S] cluster-bridged dimeric heterocomplexes with the monothiol glutaredoxin GRX5. The structure and cluster coordination of the two [2Fe-2S] heterocomplexes as well as their molecular function are, however, not defined yet. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
88
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 50 publications
4
88
0
Order By: Relevance
“…4). It was also possible to obtain a structural model of protein complexes that bind a Fe–S cluster, via an experimentally driven docking approach (exploiting the HADDOCK program [115]), by integrating NMR chemical shift perturbation analysis with other experimental data derived from EPR, NMR tailored to paramagnetic systems and mutagenesis [116].
Fig.
…”
Section: The Contribution Of Solution Nmr To Understand Molecular Aspmentioning
confidence: 99%
See 1 more Smart Citation
“…4). It was also possible to obtain a structural model of protein complexes that bind a Fe–S cluster, via an experimentally driven docking approach (exploiting the HADDOCK program [115]), by integrating NMR chemical shift perturbation analysis with other experimental data derived from EPR, NMR tailored to paramagnetic systems and mutagenesis [116].
Fig.
…”
Section: The Contribution Of Solution Nmr To Understand Molecular Aspmentioning
confidence: 99%
“…In humans, the functional role of the mitochondrial BOLA1 and BOLA3 proteins is still not clearly defined, but it was found that they form a hetero-dimeric complex with GLRX5 in both apo and [2Fe–2S]-cluster bound states [81]. NMR data, combined with other spectroscopic information, allowed us to obtain an experimentally driven docking model of [2Fe–2S] cluster-bridged dimeric BOLA1–GLRX5 and BOLA3–GLRX5 complexes, showing that the BOLA1–GLRX5 complex coordinates a reduced, Rieske-type [2Fe–2S] + cluster, while an oxidized, ferredoxin-like [2Fe–2S] 2+ cluster is present in the BOLA3–GLRX5 complex [116]. It also appeared that the [2Fe–2S] BOLA1–GLRX5 complex is preferentially formed over the [2Fe–2S] BOLA3–GLRX5 complex, as a result of a higher cluster binding affinity.…”
Section: The Contribution Of Solution Nmr To Understand Molecular Aspmentioning
confidence: 99%
“…15,25,28,29,33,34 Furthermore, [2Fe-2S]-bridged Grx homodimers and [2Fe-2S]-bridged Grx-BolA heterocomplexes can transfer Fe-S clusters to specific apo acceptor proteins. 11,15,18,23,27,33,35,36 Of note, the [2Fe-2S] Grx3-Fra2 complex in S. cerevisiae specifically transfers its cluster to the transcription factor Aft2 when these proteins are mixed.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The most common role for iron-sulfur proteins is transport, biosynthesis and insertion into the final target proteins of the clusters themselves (tagged as substrate). [22][23][24][25][26] This is the result of both the chemical complexity of the iron-containing clusters, thus requiring elaborate biosynthetic and degradation pathways, and the potential toxicity of free iron ions. The second most common roles for iron-sulfur proteins are structural and regulatory.…”
mentioning
confidence: 99%
“…For the latter, the clusters are transiently bound by various proteins along the biosynthetic pathway, also depending upon the final target for cluster insertion. 25,26,29 The electron transfer capabilities of ironsulfur proteins are important but not the only determinant of the higher abundance in the mitochondrion of iron-sulfur proteins with respect to all iron-proteins.…”
mentioning
confidence: 99%